Body composition of professional football (soccer) players determined by dual X-ray absorptiometry - Wittich, A.; Oliveri, M. B.; Rotemberg, E.; Mautalen, C. (2001)
A three-compartment body composition analysis of 42 professional football (soccer) players and 33 age- and body mass index-matched control subjects was determined by dual X-ray absorptiometry (DXA). The equipment provided a direct measurement of fat, lean, and bone mass. Fat mass was significantly higher in the controls subjects whereas lean mass and bone mass were markedly higher in the players. The percentage of body weight fat varied from 6.1 to 19.5% in the football players and from 9.1 to 29.9% in the control subjects. The respective averages were 12.0 +/- 3.1 and 19.2 +/- 5.6% (p < 0.001). The midfielders had a significantly higher percentage of fat (13.6 +/- 3.3%) than backs or forwards (11.1 +/- 2.8 and 11.0 +/- 2.3%, p < 0.05 and p < 0.06, respectively). In the football players, the correlation between age and fat mass was significant (r = 0.53, p < 0.001), whereas there was no correlation between fat and age in the control subjects (r = 0.13 p > 0.1). This article provides, for the first time, DXA analysis of body composition of football players in relation to their age and function. The results should be of interest to coaches because they will help improve athletes' performance. J Clin Densitom 2001 Spring;4(1):51-5